Antonio Gramsci's Memory of the Future: From Fordism to the Digital Age - Finelli, Roberto (International Gramsci Journal, 2025)
In “Americanism and Fordism”, Antonio Gramsci reverses his conception of intellectuals and theorises the capacity of capital to generate culture directly through its economic and productive activities, without the need to resort to other cultural "agencies" and mediating institutions. For the author of this essay, adopting this valuable insight means understanding how the abstraction of wealth, at the heart of the capitalist system, results in the emptying of the concrete world and its simultaneous reduction to a deceptive surface appearance. Through this dialectic dyad of emptying and superficialisation, the essay attempts to interpret the well-worn postmodernist ideology and the ideology of the infosphere that claims to replace it today, with the same effect of concealing the true reality of capitalist social relations.